Supernatural. Season four [videorecording (DVD)] - Kripke, Eric (Distributed by Warner Home Video, 2009)
After enduring unspeakable torture, Dean escapes from Hell, rescued by an angel who recruits Sam and Dean into Heaven's battle against Hell for the future of humankind. Amid whispers that a certain Fallen Angel will soon be freed from his prison deep in Hell. If Sam and Dean can't stop Lucifer from walking free, he'll bring on the Apocalypse. Meanwhile, the Winchester brothers reunite and hit the road, battling the supernatural wherever they go. They encounter demons, spirits, Dracula himself and even a drunk, heavily armed 7-foot-tall teddy bear. All the while, the ultimate war draws them into its horror.